Molecular cloning and characterization of the insecticidal crystal protein gene of Bacillus thuringiensis var. tenebrionis - Sekar, Vaithilingam (1987)
The insecticidal crystal protein gene of the coleopteran-toxic Bacillus thuringiensis var. tenebrionis has been isolated, and the nucleotide sequence has been determined. A total DNA library from var. tenebrionis was made in the plasmid vector pUC12. By using a synthetic 27-base oligonucleotide corresponding to a stretch of nine N-terminal amino acids of a tryptic fragment of purified crystal protein of var. tenebrionis as a probe, recombinant colonies were screened by in situ hybridization for the presence of the crystal protein gene. Positive clones obtained from this screening were further tested for toxicity. One recombinant, NSBP544 (which contained a 5.9-kilobase BamHI insert), was toxic to larvae of Colorado potato beetle. Immunoblot analysis revealed that this clone produces two crystal-specific antigens of 65 and 73 kDa as do sporulating var. tenebrionis cells. However, purified crystal inclusions from var. tenebrionis contain a primary peptide component of 65 kDa. A 1932-base-pair open reading frame with a coding capacity of 73,119 Da has been identified by nucleotide sequencing analysis of the cloned crystal protein. In addition, mung bean nuclease mapping indicates that transcription of the crystal protein of var. tenebrionis initiates 130 base pairs upstream from the translational start site. Southern blot analysis using an internal 0.7-kilobase EcoRI fragment of pNSBP544 as a probe revealed that the crystal protein gene is located on a 90-MDa plasmid.